Conjoined Twin: Late Presentation and Challenges in Management (Journal of Nobel Medical College, 2016)
Conjoined twin is a rare occurrence and its management presents with unique challenges. We report a case of a 23 year primigravida with a thoracophagus conjoined twin with complex cardiac fusion who presented to us at 34weeks of gestation. Condition was diagnosed by ultrasound; degree of fusion was assessed by computed tomography. Inspite of poor prognosis of the babies, patient was delivered by lower segment cesarean section to avoid maternal genital tract trauma.Journal of Nobel Medical College Vol.5(2) 2016; 60-63